Increased risk of early-onset preeclampsia in pregnant women with COVID-19 - Niraj N. Mahajan; Shweta Kesarwani; Padmaja Kumbhar; Periyasamy Kuppusamy; Madhura Pophalkar; Pratiksha Thamke; Ruchi Asawa; Saumya Sharan; Smita D Mahale; Rahul K Gajbhiye (Taylor & Francis Group, 2023)
Objective To estimate incidence, risk of early and late-onset preeclampsia (PE) and understand their relationship with severity of COVID-19. Methods Pregnant women with COVID-19 (n = 1929) were enrolled from 1 April 2020 to 24 February 2022. Primary outcome measure was incidence and risk of early onset PE in women with COVID-19. Results The incidence of early and late-onset PE was 11.4% and 5.6%. Moderate to severe COVID-19 was associated with eight times higher risk of early onset PE [aOR = 8.13 (1.56-42.46), p = 0.0129] compared to asymptomatic group. Conclusions Risk of early onset PE was higher in pregnant women with symptomatic COVID-19 as compared to asymptomatic women.